Right Atrioventricular Valvular Dysplasia in a New Zealand White Rabbit - Scott D. Reed; Melanie E. Blaisdell (Case Reports in Veterinary Medicine)
A sixteen-week-old, male New Zealand White rabbit was euthanized following an acute onset of respiratory distress and cyanosis. On necropsy, the rabbit had marked right atrioventricular eccentric hypertrophy, absence or rudimentary presence of the septal leaflet of the right atrioventricular valve, focally extensive left ventricular infarction, diffuse hepatic chronic passive congestion, and diffuse pulmonary edema. To our knowledge, right atrioventricular valvular hypoplasia, dysplasia, or aplasia has not been previously described in rabbits.